Growth of channel catfish in mixed sex and monosex pond culture - Goudie, C; Simco, B; Davis, K; Carmichael, G (1994)
Growth of male and female channel catfish (Ictalurus punctatus) was monitored for 6 months in triplicate 0.04-ha ponds (7500 fish/ha) stocked with mixed sexes (60-65% male), monosex males (90-98% male) or monosex females (98-100% female). Average weight and length and total weight were not different among treatment groups at any of the monthly samples. Harvest size of males was similar in ponds stocked with mixed sexes (mean±s.e.; 579±10 g and 324±2 mm, n=184), monosex males (596±9 g and 326±2 mm, n=282) and monosex females (607±48 g and 333±6 mm, n=3), parallel to the pattern observed for females in ponds stocked with mixed sexes (474±10 g and 305±2 mm, n=116), monosex males (458±21 g and 302±5 mm, n=18) and monosex females (494±7 g and 311±1 mm, n=297). Males were significantly heavier and longer than females in ponds with mixed sexes and with monosex males, but females and the small number of males in monosex female ponds were not statistically different in size. Feed conversion efficiencies were similar among treatment groups at each monthly sample, but the overall average for ponds with monosex males (0.743±0.01) was significantly higher than ponds with mixed sexes (0.670±0.02) and monosex females (0.676±0.01). Intrinsic growth patterns for both sexes were retained in monosex and mixed sex culture, demonstrating that the superior growth of males has a genetic component and is not due simply to more aggressive feeding behavior. The average weight of channel catfish harvested from monosex male ponds was about 8.5% higher than fish in mixed sex ponds and 15% higher than fish in monosex female ponds, suggesting that culture of monosex male channel catfish could provide an economic benefit. © 1994.